Pcningkatan Kctcrampilan Mcnulis Artikel Ilmiah Konseptual pada Mahasiswa S-1Keperawatan Stikes Bina Sehat Ppni Mojokerto dengan MenggunakanStrategi Terbimbing dan Strategi Penugasan - Zainudin, Moh. (JURNAL KEPERAWATAN BINA SEHAT, 2017)
AbstractThis research is motivated by the phenomenon of S-1 Nursing students who have not been able to create conceptual scientific articles. It makes the researcher interested to do research of class action, so that the student is able to make the scientific article conceptually well. This study aims to improve the skills of conceptual writing scientific articles on S-1Nursing student Bina Sehat STIKES PPNJ Mojokerto using guided strategy and strategy assignments. Guided strategy is a strategy that contains a series of activities providing guidance to students through the stages of writing, based on the writing process approach. While the assignment strategy is a strategy of assigning tasks to students to do something. The method used in this research is a classroom action research methods that include four stages, namely: (l) planning, (2) the stage of action, (3) the stage of observation, and (4) the stage of reflection. The results of analysis and discussion, indicate a very sharp increase, both student participation, as well as the skills of writing conceptual scientific articles. Based on the recapitulation of student participation, student. participation in the learning process has increased from the average score of 6.04 on pratindakan, to 11.73 (up by 5.69) in cycle 1. Similarly, the number of students who scored above 3 (above the medium category), an increase or 5 or 14% in pratindakan, to 32 or 91 % in the first cycle, while based on the recapitulation of the conceptually-making skills of scientific articles can be seen that, an increase from an average score or7.92 On pratindakan, increased 23.64 in cycle I (up by 15.72). Similarly, the number or students who scored above 20, increased from none or 0% in pratindakan, 10 31 people or 88% in cycle I. Thus it can be concluded that, guided strategy and assignment strategy is very effective to improve The skill of creating conceptual scientific articles.Keywords: Classroom Action Research, Conceptual Scientific Articles, Guided Strategics, Assignment Strategics.